A Review on Usage and Expected Benefits of Artificial Intelligence in Agriculture Sector - Sanjiv Sharma and Jashandeep Singh (International Journal of Advanced Science and Technology, 2020)
This paper is an attempt to synthesise the previous studies conducted by previous authors and the major purpose is to explore the current trends of usage and expected benefits of Artificial Intelligence (AI) in agriculture using systematic review. An extensive literature review has been carried by identifying studies conducted on usage and benefits of AI in the farming sector. The analysis reveals that is a clear pattern of concentration of studies in three major areas such as crop and soil monitoring, predictive agricultural analytics and supply chain efficiencies. Many such studies are more theoretical and are based more on AI capabilities. No comprehensive research so far has been conducted to establish what could be the best and impactful medium to deliver various observations derived from the application of AI tools.